STORAGE CHARACTERISTICS OF FEW RICE VARIETIES OF CHHATTISGARH IN RAW AND PARBOILED CONDITIONS - GEETESH SINHA, A. K. AGRAWAL, K. LAVANYA and (The Journal of Research, PJTSAU, 2017)
Rice is one of the most important food crops in the world and the staple diet for nearly half the world’s population. Few rice varieties (Mahamaya and Swarna) were taken up to explore the effects of storage on milling and cooking qualities of raw and parboiled rice. The stored samples were tested for milling and cooking qualities at 0, 20 and 40 days of storage. During milling quality evaluation, head yield of raw and parboiled samples was decreased which is also reflected by higher broken percentage with increase in storage period. Leaching loss and water uptake ratio of raw as well as parboiled grains depicted, in general, decreasing trend with increasing storage period in both varieties. The bran oil content of raw and parboiled grain was also found to decrease throughout the storage period for both varieties of rice in raw and parboiled conditions.